2016
DOI: 10.1177/1078155216665247
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electronic health record implementation on pharmacist interventions related to oral chemotherapy management

Abstract: Background With the ever growing arsenal of oral chemotherapy agents now available, cancer treatment is being increasingly managed in the outpatient setting. However, oral chemotherapy use is often associated with several potential obstacles and complications. In order to provide optimal patient safety and oral chemotherapy monitoring, our institution implemented an oral chemotherapy program managed by clinical pharmacists electronically through Epic Beacon. Objective To describe implementation of a novel phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 5 publications
2
24
0
Order By: Relevance
“…Of existing evidence, the results of our study corroborate previous studies that report the significant amount of time clinical pharmacists spend using the EHR. 7,9 Specifically, hematology/oncology clinical pharmacists in our study reported spending the greatest amount of time on patient profile review, which is corroborated by Nelson and colleagues 7 finding that clinical pharmacists spend over 11 min working up each new patient prior to rounds. Compared to our study which relied on self-reported time spent in the EHR, previous studies measured time by assigning an allotted time to each type of intervention (with the opportunity to document a specific time) 9 or performing direct observation with eye-tracking camera and contextual inquiry.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of existing evidence, the results of our study corroborate previous studies that report the significant amount of time clinical pharmacists spend using the EHR. 7,9 Specifically, hematology/oncology clinical pharmacists in our study reported spending the greatest amount of time on patient profile review, which is corroborated by Nelson and colleagues 7 finding that clinical pharmacists spend over 11 min working up each new patient prior to rounds. Compared to our study which relied on self-reported time spent in the EHR, previous studies measured time by assigning an allotted time to each type of intervention (with the opportunity to document a specific time) 9 or performing direct observation with eye-tracking camera and contextual inquiry.…”
Section: Discussionsupporting
confidence: 81%
“…7 Supporting the amount of time clinical pharmacists spend within the EHR is a standardized intervention capture template at the Veterans Health Administration, which documented a mean of 1.6 interventions per pharmacistpatient encounter. 8 A comparative study by Finn et al 9 which evaluated interventions before and after implementation of Epic Beacon showed a 560% increase in the number of pharmacist interventions, a 400% increase in the number of identified chemotherapy order errors, and an increase from 1.2 to 5.7 h spent daily on oral chemotherapy review. Taken together, the compilation of this evidence suggests that clinical pharmacists spend the majority of their time within the EHR.…”
Section: Introductionmentioning
confidence: 99%
“…EPR-based handover between staff is associated with reduced clerical errors, greater satisfaction and improved efficiency, accuracy and safety; (around 400 work hours saved annually in one service) 105. There is an improved identification of significant prescribing errors, which improves patient safety,106 and in an ITU study, the medication error rate significantly decreased post-implementation, including ordering, dispensing and administration 107…”
Section: Resultsmentioning
confidence: 99%
“…The value of the oncology pharmacist in the care of patients with cancer and within the oncology care team has been documented in several studies [ 5 ]. Oncology pharmacists have demonstrated their value in providing clinical care that has directly impacted patient outcomes, supportive care management, laboratory monitoring, and increased documentation in the electronic medical record [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Patient education, a common component of most oncology pharmacist positions, has been shown to be associated with high rates of patient satisfaction, improved learning outcomes, and leads to increased medication adherence and disease-based outcomes [ 6 , 17 , 19 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
mentioning
confidence: 99%
“…Patient education, a common component of most oncology pharmacist positions, has been shown to be associated with high rates of patient satisfaction, improved learning outcomes, and leads to increased medication adherence and disease-based outcomes [ 6 , 17 , 19 , 25 , 26 , 27 , 28 , 29 , 30 ]. Oncology pharmacists have become important members of informatics teams, and their integral role has been shown to be associated with increased rates of medication error identification [ 9 , 30 , 31 ]. Pharmacist-driven cost-savings have been reported in numerous studies, including those using pharmacists to manage oral anticancer therapies, by providing effective inpatient and ambulatory care and implementing quality improvement programs [ 18 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
mentioning
confidence: 99%